40Ar/39Ar geochronology of the Main Cental Thrust (MCT) region: Evidence for late Miocene to Pliocene disturbances along the MCT, Marsyangdi River valley, west-central Nepal Himalaya - Edwards, Rebecca M. (Journal of Nepal Geological Society, 1995)
A series of 40Ar/39Ar radiometric age data on biotites and muscovites from the MCT zone in the Marsyangdi River valley in west-central Nepal indicates that disturbances along the MCT occurred in the late Miocene to Pliocene, significantly post-dating the major deformation event of 20 Ma. The biotite and muscovite cooling ages from within 5 km on either side of the MCT range from 2.6 Ma to 9.4 Ma. Biotite cooling ages as young as 2.9 and 3.1 Ma have been found within one km of the MCT. Other ages are younger than 5 Ma. and almost all cooling ages from the area younger than 9.4 Ma.